God With Us : An Introducction to Adventis Theology. - Peckham, Jhon C. (Andrews University Press, 2023)
They comprise, perhaps, the most profound assembly of three words in any language. They express the inexpressible sum of the Gospel. They describe the absolute foundational idea in the resolution of the great universal conflict between good and evil.